2018
DOI: 10.1111/bcp.13731
|View full text |Cite
|
Sign up to set email alerts
|

Proposed biosimilar pegfilgrastim shows similarity in pharmacokinetics and pharmacodynamics to reference pegfilgrastim in healthy subjects

Abstract: PK/PD similarity of Sandoz proposed biosimilar pegfilgrastim and reference pegfilgrastim was confirmed. No clinically meaningful differences in safety, tolerability and immunogenicity were observed in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 37 publications
8
43
1
Order By: Relevance
“…None of the articles reported unexpected AEs related to either drug, such as spleen rupture. The most common adverse reaction induced by PEGylated G-CSF is skeletal and/or muscle pain [23,46]. However, the results of the present study showed that PEGylated G-CSF did not significantly increase the incidence of skeletal and/or muscle pain (P = 0.32), and the articles that did report this AE noted only mild to moderate, rather than unbearable, pain.…”
Section: Discussioncontrasting
confidence: 76%
“…None of the articles reported unexpected AEs related to either drug, such as spleen rupture. The most common adverse reaction induced by PEGylated G-CSF is skeletal and/or muscle pain [23,46]. However, the results of the present study showed that PEGylated G-CSF did not significantly increase the incidence of skeletal and/or muscle pain (P = 0.32), and the articles that did report this AE noted only mild to moderate, rather than unbearable, pain.…”
Section: Discussioncontrasting
confidence: 76%
“…The most frequently reported TEAE was headache, followed by back pain, bone pain, myalgia and pain in extremity, all of which were reported with frequencies >10% across the treatment groups. The findings of the current study are consistent with those of the Phase I PK/PD study that compared Sandoz biosimilar with the EUreference biologic exclusively 18 and with other Phase I studies comparing biosimilar pegfilgrastim medicines with the reference biologic (Neulasta). This includes published Phase I studies demonstrating similar PK/PD, safety, and immunogenicity between reference biologic and Cinfa Biotech biosimilar pegfilgrastim (B12019/Pelmeg), 26,27 Accord Healthcare biosimilar pegfilgrastim (INTP5/Pelgraz), 28,29 and Mylan biosimilar pegfilgrastim (MYL-1401H/Fulphila).…”
Section: Discussionsupporting
confidence: 88%
“…The study results also demonstrated PK/PD similarity between US-reference and EU-reference biologics, providing the PK and PD component of the scientific bridge between both biologics, allowing consideration of the results of the efficacy safety trials performed with the EU-reference biologic as comparator. 18,20,21 PK similarity was demonstrated between Sandoz biosimilar and US-reference pegfilgrastim, Sandoz biosimilar and EU-reference pegfilgrastim, and US-reference and EU-reference pegfilgrastim for the primary PK parameters AUC 0-inf , AUC 0-last , and C max , as the 90% CIs for the GM ratios of all 3 comparisons were contained within the predefined PK similarity margins (0.80- 1.25). The values of the secondary PK parameters t max and t 1/2 were consistent across the 3 treatment Within the predefined margins of PK similarity, the GM AUCs and the GM C max for Sandoz biosimilar pegfilgrastim were approximately 5-7% higher than for the reference biologics; however, the slightly higher exposure did not translate into any apparent differences in the PD effect or the safety profile.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…13,49 Pegfilgrastim-bmez showed similar pharmacokinetics and pharmacodynamics to pegfilgrastim in healthy volunteers, with no clinically meaningful differences in safety, tolerability, or immunogenicity. 50 Two randomized phase III trials (PROTECT-1 and PROTECT-2) demonstrated equivalent efficacy and safety between pegfilgrastim-bmez and pegfilgrastim in patients with breast cancer receiving myelosuppressive chemotherapy. 51,52 In PROTECT-1, patients randomized to receive pegfilgrastim-bmez had equivalent duration of severe neutropenia during cycle 1 of chemotherapy as those receiving pegfilgrastim (difference, 0.07 days; 95% CI: -0.12 to 0.26).…”
Section: Filgrastim-aafimentioning
confidence: 99%